Analysis of infrastructure-superstructure on platform and practices of Line webtoon Indonesia - Muhammad Subhan Asra (Jurnal Mantik, 2024)
The position of Digital platforms in the economy occupies a comprehensive position because it plays a role in the production, distribution and consumption of a digital commodity. This nature makes a platform an infrastructure in itself through the structuralist concept of infrastructure-superstructure. Furthermore, this concept can reveal how the webtoon platform significantly shapes the webtoon itself as a commodity format as shown by its three main characteristics: color, scrolling, and weekly. These three characteristics make the webtoon platform require a lot of labor to run its production mode smoothly. This not only impacts the welfare of webtoon comic artists who are required to work hard, but also has its own imperialistic side when webtoon platforms actively employ Indonesian comic artists with lower salaries, an inevitable result of the webtoon platform's mode of production itself